Strategi Jaringan Radio Komunitas Indonesia (JRKI) dalam Menyelamatkan Eksistensi Radio Komunitas - EDDYONO, ARYO SUBARKAH (Universitas Muhammadiyah Yogyakarta, 2012)
Community radio movement could be considered as media of resistance / counter hegemony. However, in fact, some community radios are far from expectations. Two community radio stations in Yogyakarta, which are Panaganti Radio in Terban and Angkringan Radio in Timbulhardjo, are not able to become media of resistance (Eddyono, 2011). Radio fails because government rules are too restrictive towards community radio. As a result, community radio cannot solve its own internal problems in order to survive for a long period. Moreover, this research could not get an answer about the role of Jaringan Radio Komunitas Indonesia (Indonesian Community Radio Network) in making a series of strategies to save the existence of community radio under its network, including Angkringan Radio and Panaganti Radio. This study used qualitative research and adopted Gramsci’s perspective on social movements and organic intellectual to understand the strategies which are used by JRKI to save the existence of community radio. As a result, JRKI strategies still have many weaknesses. JRKI is running out of energy in saving the existence of community radio. Keywords: Community Radio, Counter Hegemony, Democratization of Broadcasting, Battle for Positions, Organic Intellectual